Iliac Branch Devices With Standard vs Fenestrated/Branched Stent-Grafts: Does Aneurysm Complexity Produce Worse Outcomes? Insights From the pELVIS Registry. (December 2020) - Spanos, Konstantinos; Kölbel, Tilo; Scheerbaum, Martin; Donas, Konstantinos P.; Austermann, Martin; Rohlffs, Fiona; Verzini, Fabio; Tsilimparis, Nikolaos
Purpose: To compare the outcomes of iliac branch devices (IBD) used in combination with standard endovascular aneurysm repair (EVAR) vs with fenestrated/branched EVAR (f/bEVAR) to treat complex aortoiliac aneurysms.Materials and Methods: The pELVIS Registry database containing the outcomes of IBD use at 8 European centers was interrogated to identify all IBD procedures that were combined with either standard EVAR or f/bEVAR. Among 669 patients extracted from the database, 629 (mean age 72.1±8.8 years; 597 men) had received an IBD combined with standard EVAR vs 40 (mean age 71.1±8.0 years; 40 men) who underwent f/bEVAR with an IBD. The mean aortic aneurysm diameters were 46.4±13.3 mm in the f/bEVAR patients vs 45.0±15.5 mm in the standard EVAR cases. The groups were similar in terms of baseline clinical characteristics and aneurysm morphology. The Kaplan-Meier method was used to compare patient survival, IBD occlusion, type III endoleak, and aneurysm-related reinterventions in follow-up. The estimates are presented with the 95% confidence interval (CI).Results: Technical success was 100% in the f/bEVAR+IBD group and 99% in the EVAR+IBD group (p=0.85). The 30-day mortality was 0% vs 0.5%, respectively (p=0.66), while the 30-day reintervention rates were 7.5% vs 4.1% (p=0.31). The mean follow-up was 32.1±21.3 months for f/bEVAR+IBD patients (n=30) and 35.5±26.8 months for EVAR+IBD patients (n=571; p=0.41). The 12-month survival estimates were 93.4% (95% CI 93.2% to 93.6%) in the EVAR+IBD group vs 93.6% (95% CI 93.3% to 93.9%) for the f/bEVAR+IBD group (p=0.93). There were no occlusions or type III endoleaks in the f/bEVAR+IBD group at 12 months, while the estimates for freedom from occlusion and from type III endoleak in the EVAR+IBD group were 97% (95% CI 96.8% to 97.2%) and 98.5% (95% CI 98.4% to 98.6%), respectively. The 12-month estimates for freedom for aneurysm-related reintervention were 93% (95% CI 92.7% to 93.3%) in the EVAR+IBD group vs 86.4% (95% CI 85.9% to 86.9%) in the f/bEVAR+IBD patients (p=0.046).Conclusion: Treatment of complex aortoiliac disease with f/bEVAR+IBD can achieve equally good early and 1-year outcomes compared to treatment with IBDs and standard bifurcated stent-grafts, except for a somewhat higher reintervention rate in f/bEVAR patients.